0604 Treatment Patterns Among Patients With Narcolepsy Treated With Sodium Oxybate. (12th April 2019) - Bae, Charles; Epstein, Josh; Morris, Susan; Profant, Judi; Menno, Diane; Roy, Asim
Abstract: Introduction: There is limited real-world data on dosing-related practices and perceptions among patients with narcolepsy treated with sodium oxybate (SXB). This study characterized dosing patterns among narcolepsy patients taking SXB. Methods: An IRB-approved, cross-sectional, web-based survey targeting 100 patients ≥18 years, with narcolepsy taking SXB for ≥12 months, was conducted. Participants were recruited through community collaborations and patient panels. Participants were asked about their usual SXB dosing regimen and the frequency, reasons, methods and perceptions of varying their SXB dosing regimen to accommodate a change in routine. A subset (N=25) was asked telephonically about how the inability to adjust their SXB regimen would impact their lives. Descriptive statistics summarized survey responses. Voice responses were analyzed thematically. Results: The cohort (N=110) was 80% female with a mean (±SD) age of 36.9 (±8.9) years. The majority took twice-nightly doses (95%) that were equally divided (80%) with 2.5-4 hours between doses (79%). Of 82 participants that reported varying their SXB dosing at least once in the past 6 months, 29% reported varying at least once-weekly and 35% reported varying several times per month. Staying up late (76%) and waking up early (67%) to be able to attend social events (49%), work events (46%), and eat meals within 2 hours of bedtime (46%) were the most common reasons for varying dosing. Changing timing of the first dose (84%), second dose (69%) and skipping the second dose (44%) were the preferred methods of adjusting. Seventy-nine percent of participants perceived their ability to vary dosing schedules as important. Of 25 participants who provided voice responses, 68% expressed that losing the ability to vary SXB dosing would have a highly negative impact on their lives. Conclusion: Participants frequently vary their usual SXB dosing regimen to accommodate changes in their routine. Participants perceive the ability to vary as important and predict facing significant limitations in day-to-day activities if unable to vary. Further investigation to identify real-world SXB dosing, association with goal attainment, and impact on sleep and other outcomes is warranted. Support (If Any): Jazz Pharmaceuticals.